THE USE OF TECHNOLOGY IN A PARTICIPATORY THROUGH FARMERS MANAGE-EXTENSION ACTIVITIES (FMA) (CASE STUDY OF FEATI PROGRAM IN BPTP BANTEN) - Astrina Yulianti; Dewi Haryani; Sad Hutomo; U. Humaedah (Pusbindiklat - LIPI, 2012)
The study was an impact evaluation of the implementation of dissemination innovation technology in a participatory through the FEATI program in BPTP Banten, particularly conducted through demonstration plots and learning activities of FMA. The study purposed to describe the implementation, to evaluate the impact of adoption of technology at the farmers level, and to find out the enhance of the productivity or the production and the farmers income of FMA’s farmers as a the result of learning activities and demonstration plots. The assessment was accomplished by using FGD method in three sub districts of FEATI locations in Serang. The results showed that demonstration plots and learning activities in a participatory became acceptable for the farmers and effective as technology dissemination activities. The impact resulting from these two activities were increasing of the productivity or the production and the farmers income.